Reward dan Punishment Terhadap Motivasi Kerja Untuk Meningkatkan Kinerja Karyawan di Rumah Sakit Daerah - Rahayu, Yuli; Rismawati; Shine Pintor Siolemba Patiro (CV. Dalle’ Deceng Abeeayla, 2025)
This study aims to determine the effect of reward and punishment on work motivation and employee performance, and to analyze whether work motivation can improve employee performance at RSD dr. H. Soemarno Sosroatmodjo Tanjung Selor. Using a quantitative approach and survey method, data were collected through a questionnaire as the main instrument. In addition, observations were conducted to examine the actual conditions in the field. The collected data were then tested for validity, reliability, and classical assumptions to ensure data accuracy. Data analysis techniques included t-test, F-test, path analysis, and coefficient of determination test (R²). The results showed that reward had a significant effect on motivation (p = 0.000) and employee performance (p = 0.001), but not indirectly through motivation (p = 0.677). Punishment also had a significant effect on motivation (p = 0.031) and directly on performance (p = 0.031), but not indirectly (p = 0.364). Motivation was found to have no significant effect on performance (p = 0.669) due to the structured work system through KPI.